Galactooligosaccharide and a combination of yeast and beta-glucan supplements enhance growth and improve intestinal condition in striped catfish Pangasianodon hypophthalmus fed soybean meal diets - Sutriana, A; Hashim, R; Akter, MN; Nor, SAM (Springer Japan Kk, 2024)
Indexed by WOS/Scopus/ERA